2014
DOI: 10.7567/jjap.53.050301
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in absolute atom densities in H2 and N2 mixture gas plasmas by surface modifications of reactor wall

Abstract: Real time vacuum ultraviolet absorption spectroscopic (VUVAS) measurements revealed that temporal changes in absolute atom densities in H2 and N2 mixture gas (H2/N2) plasmas were affected by the conditions of the reactor inner wall-surface made of anodically-oxidized aluminum. Depending on preceding processes prior to the H2/N2 plasma process, N and H atom densities decreased for a nitrided wall surface, while no change occurred for a hydrogenated surface. Thus, the process history was revealed in the loss-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…26) As reported by Suzuki et al, it was demonstrated that these densities were maintained autonomously by a feedback controller system, even when chamber wall conditions were disturbed. 27,28) To apply a plasma etching process, etched featured profiles were tailored by lateral etching amount in a trend of processing time (Fig. 8).…”
Section: Plasma Processing In Semiconductor Manufacturingmentioning
confidence: 99%
“…26) As reported by Suzuki et al, it was demonstrated that these densities were maintained autonomously by a feedback controller system, even when chamber wall conditions were disturbed. 27,28) To apply a plasma etching process, etched featured profiles were tailored by lateral etching amount in a trend of processing time (Fig. 8).…”
Section: Plasma Processing In Semiconductor Manufacturingmentioning
confidence: 99%
“…To date, electrical discharge plasma technologies have been used in a variety of fields, such as food decontamination [2], plasma electrolysis, air purification, etching [3][4][5][6][7][8][9][10], semiconductor processes [11][12][13][14], and polymer film removal [15][16][17][18]. In our previous studies, non-equilibrium atmospheric pressure plasma was applied to glass surface cleaning [19,20], copper reduction [21], as well as silicon dioxide (SiO2) [22], and polymer etching [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group reported that etching performance on organic materials depended greatly on their temperature. [10][11][12] This temporal behavior in the substrate temperature can be monitored by our developed temperature monitoring system, with a precision of 0.01 °C and a speed of 1 ms. 13) During plasma processing, the substrate temperature is rapidly increased by energetic ion bombardments and radiative heat-fluxes from the plasma. 14,15) To maintain the substrate at a set temperature, a temperature control system was constructed.…”
mentioning
confidence: 99%
“…16) A temperature-controlled organic etching system with a dual-frequency type capacitively coupled plasma (CCP) reactor were used for the organic pattern etching and trimming processes. 11,12,17,18) H 2 and N 2 gas was supplied to the reactor at flow rates of 75 and 25 sccm, respectively, and the pressure in the reactor was maintained at 2 Pa. A power of 100 MHz for plasma excitation was supplied to the top electrode, and a power of 2 MHz for biasing was supplied to the bottom electrode, on which the 100 mm diameter Si substrate was chucked electrostatically.…”
mentioning
confidence: 99%